Composite positive electrode material and preparation method thereof, positive plate and secondary battery

By doping metal ions and boron elements into the ternary single-crystal positive electrode material and covering it with boride, the problem of poor stability of the material at high voltage is solved, the chemical stability and electrochemical properties of the material are significantly improved, and the cycle life of the battery is extended.

CN119833595AActive Publication Date: 2025-04-15ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411886344.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-15
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The existing ternary single crystal positive electrode materials have problems such as poor electrochemical stability, intensified interface side reactions and damage to the crystal structure under high voltage conditions, which affects their performance and life.

Method used

The composite positive electrode material is used to improve the particle size of the material and reduce the standard deviation of the particle size distribution by doping metal ions and boron elements into the core material and covering it with boride as the shell layer, thereby improving the chemical stability and electrochemical performance of the material.

Benefits of technology

It improves the chemical stability and electrochemical properties of the cathode material, maintains the cycle stability of the battery under high voltage, and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833595A_ABST
    Figure CN119833595A_ABST
Patent Text Reader

Abstract

The invention provides a composite positive electrode material and a preparation method thereof, a positive plate and a secondary battery. The composite positive electrode material comprises a shell layer and a core material, wherein the chemical formula of the inner core material is LiNi Co Mn < 1-a-b-c-d > M < c > B < d > O < 2 >; the shell layer is boride, and the chemical formula of the shell layer is MepBq; and the Me comprises at least one of Mn, Co, Ni, Fe, Al, Cu, Ti, Cr, Zr, Zn, Mg and W. Compared with the prior art, the composite positive electrode material provided by the invention has the advantages that the core material is doped with the metal ions and the boron element, and the shell layer is coated with the boride, so that the particle size of the material can be improved and the standard deviation of the particle size distribution can be reduced through mutual cooperation of the metal ions and the boron element, and the chemical resistance stability and the electrochemical performance of the positive electrode material are improved; and the cycling stability of the battery is maintained at high voltage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a composite positive electrode material and a preparation method thereof, a positive electrode sheet and a secondary battery. Background Art

[0002] Since the commercialization of lithium-ion batteries in the 1990s, they have been widely used in consumer electronics, aerospace, military equipment, power tools, electric vehicles and other fields due to their high energy density, high charge and discharge efficiency, low self-discharge rate, long service life and environmental friendliness. They have become one of the important technologies for electric energy storage and conversion in modern society. With the continuous development of technology and the diversification of application scenarios, the performance requirements of lithium-ion batteries are also increasing. Among them, the battery life has become a core issue of concern to users, and improving the energy density of lithium-ion batteries is one of the key ways to meet this demand.

[0003] The energy density of lithium-ion batteries can be improved from two aspects: first, by developing high-gram capacity positive and negative electrode materials to improve the storage capacity of the battery; second, by increasing the charge and discharge voltage of lithium-ion batteries to improve the mass energy density and volume energy density. In particular, increasing the charge and discharge voltage can significantly optimize the structural design of lithium batteries and further reduce the battery production cost per unit energy, thus becoming a hot research direction in the field of lithium-ion batteries.

[0004] In recent years, single crystal positive electrode materials have gradually become the research and application focus of high energy density lithium-ion battery positive electrode materials due to their advantages such as high crystal structure integrity, good stability and long cycle life. However, under high voltage conditions, single crystal positive electrode materials still face problems such as poor electrochemical stability, aggravated interfacial side reactions and crystal structure destruction, which seriously affect their performance and life extension. Therefore, in order to meet the demand for positive electrode materials in high voltage application scenarios, it is urgent to develop a single crystal positive electrode material with excellent chemical stability and electrochemical properties, so as to ensure the long-term stability of the material and the overall performance of the battery while increasing the charge and discharge voltage. Summary of the invention

[0005] One of the purposes of the present invention is to provide a composite positive electrode material to address the deficiencies in the prior art, so as to improve the problem of unstable performance of current ternary single crystal positive electrode materials under high voltage.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A composite positive electrode material, comprising an outer shell layer and a core material; wherein the chemical formula of the core material is LiNi a Co b Mn 1-a-b-c-d Mec B d O2, 0≤a≤1, 0≤b≤1, 0≤c≤0.1, 0≤d≤0.1, a+b+c+d>0; the outer shell is a boride, and the chemical formula of the outer shell is Me p B q , 1≤p≤3, 1≤q≤3; the Me includes at least one of Mn, Co, Ni, Fe, Al, Cu, Ti, Cr, Zr, Zn, Mg and W.

[0008] Preferably, the mass ratio of the outer shell layer to the inner core material is (0.01-0.5):100.

[0009] Preferably, the particle size distribution standard deviation σ of the composite positive electrode material particles and the Dv10 particle size r of the composite positive electrode material particles satisfy the relationship: 0.001≤σ / r≤0.5, wherein 0.01≤σ≤5, and the unit of r is μm.

[0010] Preferably, the Dv10 particle size r of the composite positive electrode material particles is 5-25 μm.

[0011] Preferably, the particle size distribution standard deviation σ of the composite positive electrode material particles and the mass proportion w of the outer shell layer satisfy the relationship: 10≤σ / w≤1000, wherein the mass proportion of the outer shell layer is the mass ratio of the outer shell layer to the core material.

[0012] The second object of the present invention is to provide a method for preparing a composite positive electrode material, comprising the following steps:

[0013] S1, after the lithium compound, the nickel-cobalt-manganese ternary precursor and the borate containing the Me element are uniformly mixed, the first stage of sintering is performed in an air atmosphere, and then the temperature is continuously raised to perform the second stage of sintering, and then the temperature is kept, and after cooling, the mixture is ground in an inert atmosphere to obtain a pre-sintered product;

[0014] S2. Adding boride containing Me element to the pre-sintered product, and then fully mixing, sintering in a protective atmosphere, and then keeping warm, grinding in an inert atmosphere after cooling, and finally obtaining a boride-modified composite positive electrode material.

[0015] Preferably, the molar ratio of the lithium compound, the nickel-cobalt-manganese ternary precursor, and the borate containing the Me element is Li:(Ni+Co+Mn):Me=(1.01-1.10):1:(0.005-0.2).

[0016] Preferably, the molar ratio of the lithium compound, the nickel-cobalt-manganese ternary precursor, and the borate containing the Me element is Li:(Ni+Co+Mn):Me=1.05:1:(0.01-0.1).

[0017] Preferably, in step S1, the first stage sintering temperature is 700-900°C, the heating rate is 1-5°C / min, and the sintering time is 6-8h;

[0018] The second stage sintering temperature is 1200-1400℃, the heating rate is 5-10℃ / min, the sintering time is 4-6h, the holding temperature is 300-500℃, and the holding time is 5-9h;

[0019] In step S2, the sintering temperature is 1000-1200°C, the heating rate is 1-5°C / min, and the sintering time is 8-12h; the insulation temperature is 400-600°C, and the insulation time is 4-6h.

[0020] The third object of the present invention is to provide a positive electrode sheet comprising the positive electrode material described in any of the above paragraphs.

[0021] A fourth object of the present invention is to provide a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator separated between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet mentioned above.

[0022] Compared with the prior art, the beneficial effect of the present invention is that the composite positive electrode material provided by the present invention is doped with metal ions and boron elements in the core material, and the outer shell layer is coated with borides. The cooperation between the two can increase the particle size of the material and reduce the standard deviation of its particle size distribution, thereby improving the chemical resistance and stability of the positive electrode material, while improving the electrochemical performance of the positive electrode material and maintaining the cycle stability of the battery under high voltage. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a SEM image of a composite positive electrode material according to an embodiment of the present invention. DETAILED DESCRIPTION

[0024] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.

[0025] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0026] 1. Cathode materials

[0027] In a first aspect of the present invention, a composite positive electrode material is provided, comprising an outer shell layer and a core material; wherein the chemical formula of the core material is LiNi a Co b Mn 1-a-b-c-d Me c B d O2, 0≤a≤1, 0≤b≤1, 0≤c≤0.1, 0≤d≤0.1, a+b+c+d>0; the outer shell is a boride, and the chemical formula of the outer shell is Me p B q , 1≤p≤3, 1≤q≤3; the Me includes at least one of Mn, Co, Ni, Fe, Al, Cu, Ti, Cr, Zr, Zn, Mg and W.

[0028] Boride as an outer shell layer covering the core material can reduce the side reaction between the core material and the electrolyte, improve the cycle stability and electrochemical performance of the battery. At the same time, boride can improve the thermal stability of the material, inhibit oxygen release, and enhance the safety of the battery.

[0029] In the present invention, by doping metal cations and boron elements into the core material, the particle size of the ternary positive electrode material is increased and the standard deviation of its particle size distribution is reduced, which can improve the overall uniformity of the material. The doping of metal cations can induce the formation of oxygen vacancies and metal atom vacancies, increase the active sites, form an atomic-level conductive network, and ultimately enhance the lithium storage performance. In addition, the doping of metal cations can improve the stability of the material structure, thereby significantly improving the cycle stability of the battery material.

[0030] In some embodiments, the mass ratio of the outer shell layer to the inner core material is (0.01-0.5):100, and may be 0.01:100, 0.05:100, 0.1:100, 0.2:100, 0.3:100, 0.4:100, 0.5:100, and may include but are not limited to the values ​​listed above.

[0031] In some embodiments, the particle size distribution standard deviation σ of the composite positive electrode material particles and the Dv10 particle size r of the composite positive electrode material particles satisfy the relationship: 0.001≤σ / r≤0.5, wherein 0.01≤σ≤5, and the unit of r is μm. Preferably, 0.004≤σ / r≤0.12.

[0032] The smaller the ratio of standard deviation σ to particle size r, the smaller the standard deviation or the larger the particle size under the same particle size or standard deviation. The smaller the standard deviation, the more uniform the particle size, the better the material consistency, and the more stable the performance. The larger the particle size, the better the material stability. Therefore, the smaller the ratio of standard deviation σ to particle size r, the better the material performance. However, since the standard deviation σ cannot be infinitely small, there is a lower limit. The larger the standard deviation σ, the worse the material consistency, so an upper limit is set. Beyond this range, the material performance will deteriorate significantly.

[0033] In some embodiments, the Dv10 particle size r of the composite positive electrode material particles is 5-25 μm.

[0034] In the particle size r range, the smaller the particle size, the worse the stability of the material, so a lower limit is set; however, due to process limitations, it is difficult to make the single crystal particle size particularly large, so there is an upper limit. Beyond this range, the material performance will be greatly deteriorated.

[0035] In some embodiments, the standard deviation σ of the particle size distribution of the composite positive electrode material particles and the mass proportion w of the outer shell layer satisfy the relationship: 10≤σ / w≤1000, wherein the mass proportion of the outer shell layer is the mass ratio of the outer shell layer to the core material. Preferably, 20≤σ / w≤800. The smaller the standard deviation σ is to the mass ratio of the outer shell layer, the smaller the corresponding standard deviation or the larger the particle size under the same mass or standard deviation of the outer shell layer, wherein the smaller the standard deviation, the more uniform the particle size, the better the material consistency, and the more stable the performance; wherein the greater the mass of the outer shell layer, the better the stability of the material; thus, the smaller the standard deviation σ is to the mass ratio of the outer shell layer, the better the material performance, so an upper limit is set; however, since the standard deviation σ cannot be infinitely small, there is a lower limit. Beyond this range, the material performance will be greatly deteriorated.

[0036] A second aspect of the present invention provides a method for preparing the composite positive electrode material, comprising the following steps:

[0037] S1, after the lithium compound, the nickel-cobalt-manganese ternary precursor and the borate containing the Me element are uniformly mixed, the first stage of sintering is performed in an air atmosphere, and then the temperature is continuously raised to perform the second stage of sintering, and then the temperature is kept, and after cooling, the mixture is ground in an inert atmosphere to obtain a pre-sintered product;

[0038] S2. Adding boride containing Me element to the pre-sintered product, and then fully mixing, sintering in a protective atmosphere, and then keeping warm, grinding in an inert atmosphere after cooling, and finally obtaining a boride-modified composite positive electrode material.

[0039] In some embodiments, the molar ratio of the lithium compound, the nickel-cobalt-manganese ternary precursor, and the borate containing the Me element is Li:(Ni+Co+Mn):Me=(1.01-1.10):1:(0.005-0.2). Preferably, Li:(Ni+Co+Mn):Me=1.05:1:0.01-0.1, specifically 1.05:1:0.01, 1.05:1:0.01, 1.05:1:0.02, 1.05:1:0.03, 1.05:1:0.04, 1.05:1:0.05, 1.05:1:0.06, 1.05:1:0.07, 1.05:1:0.08, 1.05:1:0.09, 1.05:1:0.1, may include but are not limited to the values ​​listed above, more preferably 1.05:1:0.05.

[0040] In the embodiment of the present invention, in step S1, the first stage sintering temperature is 700-900°C, the heating rate is 1-5°C / min, and the sintering time is 6-8h;

[0041] The sintering temperature of the second stage is 1200-1400°C, the heating rate is 5-10°C / min, the sintering time is 4-6h, the holding temperature is 300-500°C, and the holding time is 5-9h.

[0042] In the embodiment of the present invention, in step S2, the sintering temperature is 1000-1200°C, the heating rate is 1-5°C / min, and the sintering time is 8-12h; the insulation temperature is 400-600°C, and the insulation time is 4-6h.

[0043] The present invention adopts multiple staged sintering and uses boride to coat the material, and cooperates with reasonable temperature and time control to improve the morphological stability of the surface of the ternary material and improve the particle size and the standard deviation of its particle size distribution, make the shell coating layer more consistent, reduce the difference in materials, and thus improve chemical resistance stability.

[0044] 2. Positive electrode

[0045] The third aspect of the present invention provides a positive electrode sheet, comprising the composite positive electrode material described above, specifically comprising a positive electrode current collector and a positive electrode active material layer coated on at least one surface of the positive electrode current collector, and the positive electrode active material is the positive electrode material described in the present invention.

[0046] The positive electrode current collector can be any material suitable for use as a positive electrode current collector for lithium-ion batteries in the art. For example, the positive electrode current collector can include but is not limited to metal foil, and more specifically can include but is not limited to aluminum foil.

[0047] 3. Secondary battery

[0048] A fourth aspect of the present invention is to provide a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet described above.

[0049] The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector. The negative electrode active material layer may include but is not limited to one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium. Among them, the graphite can be selected from one or more of artificial graphite, natural graphite and modified graphite; the silicon-based material can be selected from one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys; the tin-based material can be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. The negative electrode current collector is usually a structure or part that collects current. The negative electrode current collector can be various materials in the art that are suitable for use as a negative electrode current collector for lithium-ion batteries. For example, the negative electrode current collector can be, but is not limited to, metal foil, and more specifically, can be, but is not limited to, copper foil.

[0050] The separator can be any material suitable for lithium-ion battery separators in the art, for example, it can be a combination of one or more materials including but not limited to polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers.

[0051] The secondary battery also includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt and an additive. Among them, the electrolyte lithium salt can be LiPF6 and / or LiBOB used in high-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, and LiPF6 used in low-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, LiPF6, and LiTFSI used in anti-overcharge electrolytes; it can also be at least one of LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. The organic solvent can be a cyclic carbonate, including PC and EC; it can also be a chain carbonate, including DFC, DMC, or EMC; it can also be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include but are not limited to at least one of film-forming additives, conductive additives, flame retardant additives, anti-overcharge additives, additives for controlling the content of HO and HF in the electrolyte, additives for improving low-temperature performance, and multifunctional additives.

[0052] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.

[0053] Example 1

[0054] The preparation method of the composite positive electrode material in this embodiment is:

[0055] Step S1: lithium carbonate, nickel-cobalt-manganese ternary positive electrode precursor, and titanium borate are fully mixed according to the stoichiometric ratio of Li: (Ni+Co+Mn):Ti=1.05:1:0.05, sintered at 800°C for 7h in an air atmosphere at a heating rate of 1-5°C / min, then continued to heat to 1300°C and sintered for 5h at a heating rate of 5-10°C / min, kept at 400°C for 7h, cooled and ground in a nitrogen atmosphere to obtain a pre-sintered product.

[0056] Step S2: Add titanium boride to the pre-sintered product, then fully mix by ball milling, sinter at 1100°C for 10 hours in a nitrogen atmosphere, with a heating rate of 1-5°C / min, and keep at 500°C for 5 hours, and grind in a nitrogen atmosphere after cooling to finally obtain a ternary single crystal composite positive electrode material. The mass ratio of the titanium boride outer shell layer to the core material is 0.25:100.

[0057] Embodiment 2-3

[0058] The difference between this embodiment and embodiment 1 is that the stoichiometric ratio of titanium borate in step S1 is shown in Table 1 for details.

[0059] The rest is the same as in Example 1 and will not be described again here.

[0060] Embodiment 4-5

[0061] The difference between this embodiment and embodiment 1 is the sintering temperature of step S1; see Table 1 for details.

[0062] The rest is the same as in Example 1 and will not be described again here.

[0063] Embodiment 6-7

[0064] The difference between this embodiment and embodiment 1 is the sintering time of step S1; see Table 1 for details.

[0065] The rest is the same as in Example 1 and will not be described again here.

[0066] Embodiments 8 to 9

[0067] The difference between this embodiment and embodiment 1 is that titanium boride in different mass ratios is added in step S2; see Table 2 for details.

[0068] The rest is the same as in Example 1 and will not be described again here.

[0069] Embodiments 10 to 11

[0070] The difference between this embodiment and embodiment 1 is the sintering temperature of step S2; see Table 2 for details.

[0071] The rest is the same as in Example 1 and will not be described again here.

[0072] Embodiments 12 to 13

[0073] The difference between this embodiment and embodiment 1 is the sintering time of step S2; see Table 2 for details.

[0074] The rest is the same as in Example 1 and will not be described again here.

[0075] Comparative Example 1

[0076] After lithium carbonate and nickel-cobalt-manganese ternary precursors are fully mixed in a stoichiometric ratio of Li:(Ni+Co+Mn)=1.05:1, they are sintered at 800°C for 7 hours in an air atmosphere with a heating rate of 1-5°C / min, and then kept at 400°C for 7 hours. After cooling, they are ground in an inert atmosphere to obtain a once-sintered ternary material.

[0077] Comparative Example 2

[0078] The difference between this comparative example and comparative example 1 is that the ternary material obtained by the primary sintering is subjected to a secondary calcination, as shown in Tables 1 and 2 for details.

[0079] The rest is the same as Comparative Example 1 and will not be described again.

[0080] Comparative Example 3

[0081] The difference between this comparative example and Example 1 is that there is no step S2.

[0082] The rest is the same as in Example 1 and will not be described again here.

[0083] Comparative Example 4

[0084] The difference between this comparative example and Example 1 is that there is no second stage of temperature rise sintering in step S1.

[0085] The rest is the same as in Example 1 and will not be described again here.

[0086] Comparative Example 5

[0087] The difference between this comparative example and Example 1 is that titanium borate is not added in step S1.

[0088] The rest is the same as in Example 1 and will not be described again here.

[0089] Comparative Example 6

[0090] The difference between this comparative example and Example 1 is that titanium borate is not added in step S2. The rest is the same as Example 1 and will not be described again.

[0091] The specific preparation parameters of the above examples and comparative examples are summarized in Table 1 and Table 2.

[0092] Table 1

[0093]

[0094]

[0095] Table 2

[0096]

[0097]

[0098] The positive electrode materials prepared in Examples 1-13 and Comparative Examples 1-6 were assembled into lithium ion button cells and the electrical performance was tested at room temperature. The charge and discharge conditions were 0.5C and the charge and discharge range was 3.0V-4.60V. The test results are summarized in Tables 3 and 4.

[0099] Table 3 Electrical performance test results

[0100]

[0101]

[0102] Particle size measurement method: Add the weighed positive electrode material into the particle size analyzer. The dispersant in the instrument is pure water. The speed of the agitator is 3000rpm. By adjusting the refractive index, the test cycle is repeated 3 times. Finally, the particle size data of the particle size analyzer Dv10 is read, which is the particle size r.

[0103] Standard deviation calculation method: Dv10, Dv50, and Dv90 obtained from particle size measurement are calculated according to the standard deviation calculation formula: Among them, Dv10, Dv50, and Dv90 are x i , μ is the average value of Dv10, Dv50, and Dv90, n=3.

[0104] Table 4 Particle size and standard deviation test results

[0105]

[0106]

[0107] From the above test results, it can be seen that the doping of metal ions and boron elements in the ternary positive electrode material and the coating of the outer shell layer with borides can cooperate with each other to increase the particle size of the material and reduce the standard deviation of its particle size distribution, thereby improving the chemical resistance and stability of the positive electrode material, while improving the electrochemical performance of the positive electrode material and maintaining the cycle stability of the battery under high voltage.

[0108] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A composite positive electrode material, characterized in that: It includes an outer shell layer and a core material; wherein the chemical formula of the core material is LiNi a Co b Mn 1-a-b-c-d Me c B d O2, 0≤a≤1, 0≤b≤1, 0≤c≤0.1, 0≤d≤0.1, a+b+c+d>0; the outer shell is a boride, and the chemical formula of the outer shell is Me p B q , 1≤p≤3, 1≤q≤3; the Me includes at least one of Mn, Co, Ni, Fe, Al, Cu, Ti, Cr, Zr, Zn, Mg and W.

2. A composite positive electrode material according to claim 1, characterized in that: The mass ratio of the outer shell layer to the inner core material is (0.01-0.5):

100.

3. A composite positive electrode material according to claim 1, characterized in that: The standard deviation σ of the particle size distribution of the composite positive electrode material particles and the Dv10 particle size r of the composite positive electrode material particles satisfy the relationship: 0.001≤σ / r≤0.5, wherein 0.01≤σ≤5, and the unit of r is μm.

4. A composite positive electrode material according to claim 3, characterized in that: The Dv10 particle size r of the composite positive electrode material particles is 5-25 μm.

5. A composite positive electrode material according to claim 1, characterized in that: The standard deviation σ of the particle size distribution of the composite positive electrode material particles and the mass proportion w of the outer shell layer satisfy the relationship: 10≤σ / w≤1000, wherein the mass proportion of the outer shell layer is the mass ratio of the outer shell layer to the core material.

6. A method for preparing a composite positive electrode material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, after the lithium compound, the nickel-cobalt-manganese ternary precursor and the borate containing the Me element are uniformly mixed, the first stage of sintering is performed in an air atmosphere, and then the temperature is continuously raised to perform the second stage of sintering, and then the temperature is kept, and after cooling, the mixture is ground in an inert atmosphere to obtain a pre-sintered product; S2. Adding boride containing Me element to the pre-sintered product, and then fully mixing, sintering in a protective atmosphere, and then keeping warm, grinding in an inert atmosphere after cooling, and finally obtaining a boride-modified composite positive electrode material.

7. The method for preparing a composite positive electrode material according to claim 6, characterized in that: The molar ratio of the lithium compound, the nickel-cobalt-manganese ternary precursor, and the borate containing the Me element is Li:(Ni+Co+Mn):Me=(1.01-1.10):1:(0.005-0.2).

8. The method for preparing a composite positive electrode material according to claim 6, characterized in that: In step S1, the sintering temperature of the first stage is 700-900°C, the heating rate is 1-5°C / min, and the sintering time is 6-8h; the sintering temperature of the second stage is 1200-1400°C, the heating rate is 5-10°C / min, the sintering time is 4-6h, the holding temperature is 300-500°C, and the holding time is 5-9h; In step S2, the sintering temperature is 1000-1200°C, the heating rate is 1-5°C / min, and the sintering time is 8-12h; the insulation temperature is 400-600°C, and the insulation time is 4-6h.

9. A positive electrode sheet, characterized in that: The composite positive electrode material comprises the composite positive electrode material according to any one of claims 1 to 5.

10. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, characterized in that: The positive electrode sheet is the positive electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Cathode material for boracic lithium ion battery and preparation method thereof

    CN105244492A

  • A preparation method of a high-compaction high-capacity lithium manganate composite cathode material used for mixing ternary materials

    CN109244450A

  • Positive active material, preparation method thereof and electrochemical energy storage device

    CN110957474A

  • Positive electrode active material for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery using same

    CN116057729A

  • Positive electrode active material and preparation method and application thereof

    CN116504939A

Cited By

  • Nano single-crystal positive electrode material and preparation method thereof, solid-state battery and electric equipment

    CN120674481A

  • Composite positive electrode material and preparation method therefor, positive electrode sheet, and secondary battery

    WO2026129784A1